Seroprevalencia y detección de infección primaria por citomegalovirus mediante prueba de avidez IgG en el primer trimestre de embarazo - Conne L González-García; Miguel A Reyes-Méndez; Luz E Ortega-Pierres; Adriana P Rodríguez-Sánchez; Verónica Sandoval-Guido; José A Sereno-Coló (Instituto Nacional de Salud Pública, 2014)
Objective. To determine the seroprevalence and detection of primary infection by cytomegalovirus (CMV) with immunoglobulin G (IgG) avidity test during the first quarter of pregnancy in the General Hospital in Morelia, Michoacan. Materials and methods. A total of 177 patients were studied employing a modified Elisa test using a chemiluminescent microparticle immunoassay (CMIA) for the detection of CMV antibodies (IgG and immunoglobulin M [IgM]), and IgG avidity. Results. 90.4% were positive for IgG, and of these, 2.3% were also reactive for IgM, and in this group the IgG avidity test reported low avidity for 1.1% and higher avidity in the same percentage. 9.6% were seronegative. Conclusions. Similarity was found with published studies in Mexico. Health professionals should know the clinical algorithms for diagnosis and proper management of CMV infection using the IgG avidity test.